USING THE WATTPAD APPLICATION TO IMPROVE STUDENTS’ READING COMPREHENSION - Asir, Niftahul Jannah; Farahdiba, Syarifah; Sofyan, Ryan Rayhana (Universitas Negeri Makassar, 2024)
The objective of this research was to find out whether using the Wattpad application improves students’ reading comprehension. The researcher applied pre-experimental research which employed one-group pre-test and post-test. The participants of this research were from the VIII-B1 class of UPT SPF SMP Negeri 5 Makassar which consisted of 35 students who were determined using random sampling techniques. The research instrument used was multiple choice reading comprehension: narrative text. The pre-test and post-test results using the Wattpad application in developing students’ reading comprehension after being analyzed using the significant test formula show that the t-test value was 8.043 > t-table value 1.685. As a result, the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. After analyzing the n-gain value, the results show that using the Wattpad application is classified as average. In conclusion, using the Wattpad application improves students’ reading comprehension in identifying the main idea, identifying supporting details, understanding vocabulary, identifying references, and making inferences.